Meanings and Interpretation of Value Creation: The Role of Context and Value Chain Position - Svetla Trifonova Marinova; Marin A. Marinov (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
By adopting a firm-focused perspective to value creation in order to unveil the firm-specific meanings and interpretations of value creation, the paper explores how companies with a different position in a global value chain perceive the internal and external value they create. Based on interviews in three firms operating in a traditional industry, we show that value perceptions are conditioned by firm strategy and scope of activities and value creation is informed by the characteristics of the business model of the firm and by the socially constructed reality in which the business model operates. While all firms identify the importance of economic value - with value-for-money, profit, stability and wealth for the user and the organisation, of psychological value - with happiness and shared values, and of sociological value - with belonging and social responsibility, from a user, organizational and ecosystem perspective, the concrete meanings and interpretations, the sources of and approaches to creating these types of value are rather distinct to each firm and therefore, embedded and conditioned by the firm's contextual system and by the firm's position in a global value chain. Whereas an integrator SME in a global value chain is focused on creating internal and external value by orchestrating and integrating its brand value with a combination of weak and strong ties, a more diversified glocal value chain position of an emerging market firm has the potential to create greater internal and external value for the firm and the social system in which it is embedded.
Keywords: 650; Value creation; Value chain; Value perceptions